Molecular based identification and phylogenetic relationship by using ITS-rDNA and YCF1 gene of Cinnamomum parthenoxylon (Jack) Meisn. in northern Vietnam - Vu, Dinh Duy; Pham, Mai Phuong; Bui, Thi Tuyet Xuan; Vu, Dinh Giap; Nguyen, Quynh Trang; Hoang, Thi Tham (Vietnam Journal of Biotechnology, 2025)
Accurate species identification plays a critical role in conservation, evolutionary studies, and taxonomic classification. Traditional morphological identification is often unreliable, particularly at immature developmental stages, whereas DNA barcoding offers a rapid and precise alternative. In this study, we applied two DNA barcoding regions the nuclear ribosomal DNA (ITS-rDNA) and the chloroplast gene (ycf1) to identify 15 samples of C. parthenoxylon species collected from five geographic regions in northern Vietnam (Quang Ninh, Vinh Phuc, Phu Tho, Hoa Binh, and Thanh Hoa), and to investigate their phylogenetic relationships within the genus Cinnamomum. PCR amplification and sequencing success rates were 100% for both markers. The obtained sequence lengths were 588 bp for ITS-rDNA and 795 bp for ycf1. Base composition analysis showed that ITS-rDNA sequences contained, on average, T (12.1%), C (35.9%), A (16.3%), and G (35.7%), whereas ycf1 sequences comprised T (39.9%), C (15.1%), A (29.9%), and G (15.1%). ITS-rDNA sequence analysis revealed high similarity among the 15 C. parthenoxylon samples, differing by only one nucleotide, and strongly clustered with C. parthenoxylon (MLBS = 92-96%; BPP = 88-98%). In contrast, ycf1 sequences showed five nucleotide differences among the samples and indicated a close relationship with both C. parthenoxylon and C. balansae (MLBS = 67-80%; BPP = 55-74%). Genetic divergence among Cinnamomum species averaged 6% (range 0-13%) for ITS-rDNA and 2% (range 0-4%) for ycf1. These findings suggest that ITS-rDNA is a suitable marker for species identification within Cinnamomum, whereas the ycf1 region has lower resolution and is less effective for distinguishing among closely related species in this genus.